Baby geniuses - Paul, Steven; Matos, Francisca; Grasmere, Robert; Clark, Bob, 1939-2007.; Turner, Kathleen, 1954-; Lloyd, Christopher, 1938-; MacNicol, Peter, 1954-; Zala, Paul.; Tri-Star Pictures; Columbia TriStar Home Video (Firm) (Culver City, California Columbia TriStar Home Entertainment, 2010)
All babies are born knowing how to speak to each other. What adults hear as baby talk is actually conversation, and Dr. Kinder is devoted to cracking this special infant language.
Title from container.
Originally released as a motion picture in 1999.
Special features: making of featurette; Movie magic special effects mini-featurette.
Director of photography, Stephen M. Katz; music, Paul Zala.
Christopher Lloyd, Kathleen Turner, Kim Cattrall, Dom Deluise, Ruby Dee.
MPAA rating: PG for some rude behavior and dialogue CHV rating: G.
Keywords: Twins -- Drama; Infants -- Drama; DVD-video discs; Comedy films; Drama; Feature films; Video recordings for the hearing impaired; Comedy films; Video recordings for the hearing impaired